SUMIDA, PENGALAMAN TATAKELOLA SUNGAI YANG MENGINSPIRASI - Murtedjo, Tedy; Purba, Aleksander (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2012)
The Sumida River (Sumida-gawa) is a river which flows through Tokyo Japan. It branches fromthe Arakawa River at Iwabuchi and flows into Tokyo Bay. Its tributaries include the Kanda andShakujii rivers. What is now known as the "Sumida River" was previously the path of theArakawa, however towards the end of the Meiji era work was carried out to divert the main flowof the Arakawa to prevent flooding. It passes through the following seven wards of Tokyo.